Consumo de azitromicina en un establecimiento farmacéutico privado de Trujillo, enero – diciembre 2018 - Henostroza Cautivo, Elizabeth Ana (2019)
The purpose of this report was to determine the consumption of azithromycin in a pharmaceutical establishment in Trujillo from January to December 2018. The data of azithromycin-dispensed tablets and their commercial equivalents, obtained from the computerized system of an establishment, were considered. pharmaceutical during the period in question. Consumption was determined by means of the defined daily dose (DDD), this is a technical unit for measuring drug consumption, which corresponds to the maintenance dose in the main indication for a route of administration for adults. As results, azithromycin was the one with the highest annual consumption of 4.351 DDD /1000 inhabitants/day, followed by Azitor with 2.179 DDD/1000 inhabitants/day, Azicat with 0.663 DDD/1000 inhabitants/day, Astrocina 0.255 DDD/1000 inhabitants/day and zithromax with 0.208 DDD/1000 inhabitants/day. The consumption of azithromycin and its commercial equivalents showed a statistically non-significant linear trend with values of p = 0.6424 for azithromycin, Azitor a p = 0.9355, Azicat = 0.9759, Astrocina = 0.9835 and Zitromax = 0.9859 Annually we have July and March as the months of highest and lowest consumption with 202 and 142 units respectively. Azithromycin was the largest number of units dispensed annually with 1194. The month of greatest and lowest cost in azithromycin consumption were May and March with S / 1543.6 and 692.2 respectively. Likewise, the highest annual expense was for the commercial form Azitor with S/ 7714.2